Pengaruh Model Pembelajaran Kooperatif Tipe Make a Match Berbantuan Media Gambar Terhadap Hasil Belajar PKn Siswa Kelas IV di SD Negeri 1 Sapit Kecamatan Suela Tahun Pelajaran 2025/2026 - Rukhwatul Ulfah; Zohrani; Zalia Muspita; Muhammad Husni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to determine the influence of the cooperative learning model type make a match assisted by picture media on the Civics learning outcomes of fourth-grade students at SD Negeri 1 Sapit, Suela District, in the academic year 2025/2026. The type of research used is quantitative experimental with a pre-experimental design, specifically the one-group pretest-posttest type. The research sample consisted of 21 fourth-grade students. The data collection techniques used were multiple-choice tests and observation. Based on the results of the study, the average pretest score was 56.71 and the posttest score was 74.67. The Shapiro-Wilk normality test showed that T₃ > P-Value for both the pretest and posttest, indicating that both data sets were normally distributed. The hypothesis test was calculated using the paired sample t-test, which yielded a t-count of 10.15 and a t-table of 2.086, obtained from df = n - 1 = 21 – 1 = 20 with a significance level of 0.05. Since t-count = 10.15 > t-table = 2.086, it can be concluded that H0 is rejected and Ha is accepted, which means that the cooperative learning model type make a match assisted by picture media has a significant effect on Civics learning outcomes of fourth-grade students at SD Negeri 1 Sapit, Suela District, Academic Year 2025/2026.